Evaluation of antioxidant and anti-inflammatory effects of red raspberries on chronic nicotine-induced damage: an experimental study - Selli, Jale (International Journal of Research in Medical Sciences, 2019)
Background: As an addictive substance, nicotine has been recognized as a risk factor to induce oxidative tissue damage, which is a main risk factor for development of lung-related diseases. Red raspberries (Rubus idaeus L.) have been used for the treatment of several tissue damage for decreasing oxidative stress and inflammation. For this purpose, authors aimed to investigate the antioxidant and anti-inflammatory effects of raspberry on nicotine-induced lung damage in rats. Methods: 32 male Sprague–Dawley rats included in present study. The rats were divided into the following four groups, with eight rats in each group: control, raspberry 100 mg/kg, nicotine 5 mg/kg, nicotine + raspberry 100 mg/kg treated (concomitant nicotine and raspberry extract) groups. The assessment of lung structure was made on light and stereo investigator microscope, immunohistochemical analysis was performed by determining anti-Caspase-3 immunostaining. Results: The lung of the nicotine applied group exhibited emphysematous air spaces, massive congestion areas, disrupted alveoli, thickened septa and inflammatory cell infiltration. Much improvement was observed in the raspberry-treated group despite the presence of mild residual changes. Moreover, loss of massive congestion areas and decreased Caspase-3 level were detected in the raspberry-treated group. Conclusions: Our results indicate that the raspberry extract attenuate the pathological changes of nicotine in the lung rats through antioxidative and anti- inflammatory mechanisms.